BRAZILIAN CONSENSUS FOR MULTIMODAL TREATMENT OF COLORECTAL LIVER METASTASES. MODULE 3: CONTROVERSIES AND UNRESECTABLE METASTASES - TORRES,Orlando Jorge Martins (2016)
ABSTRACT In the last module of this consensus, controversial topics were discussed. Management of the disease after progression during first line chemotherapy was the first discussion. Next, the benefits of liver resection in the presence of extra-hepatic disease were debated, as soon as, the best sequence of treatment. Conversion chemotherapy in the presence of unresectable liver disease was also discussed in this module. Lastly, the approach to the unresectable disease was also discussed, focusing in the best chemotherapy regimens and hole of chemo-embolization.